Microstructure and electrochemical properties of post heat-treated li(Ni1/3Co1/3Mn1/3)O2 cathode materials for lithium ion battery - Kim, S.H.; Kim, C.-S.; Han, K.R.; Shim, K.B. (Materials Science Forum, 2006)
Li(Ni1/3Co1/3Mn1/3)O2 powders were synthesized by using an ultrasonic spray pyrolysis method, and then heat-treated at 900 or 1000°C for 20 h. The morphology of the as-synthesized powder was spherical. The post heat-treatment changed the particle size and morphology of the synthesized powders. Structural characteristics of the heat-treated powders were analyzed using XRD and SEM, and their electrochemical properties were compared. Higher first discharge capacity was obtained from the powder heat-treated at 1000°C, but its rough and rugged surface might cause a rapid decrease of the capacity retention.